Economic value of subcutaneous versus intravenous trastuzumab administration in the treatment of HER2-positive breast cancer: A systematic review - Thuy, Nguyen Thi Thu; Duyen, Tran Thi My; Chi, Nguyen Vu Lan; Dung, Pham Tri (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Introduction: Trastuzumab is the standard therapy for HER-positive breast cancer, traditionally administered intravenously (T-IV). The subcutaneous trastuzumab (T-SC), introduced in 2013, may may offer cost savings compared to T-IV. While previous studies have examined the economic value of T-SC, no quality assessment of these studies or a currency-standardized comparison across countries has been conducted. This study aimed to address these gaps by systematically reviewing and assessing the quality of economic evaluations comparing T-SC and T-IV. Methods: A systematic review of publications until May 31, 2021, was performed using databases like MEDLINE, Cochrane, and ScienceDirect, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) statement. The quality of studies was assessed using the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist. All costs were adjusted to 2019 Euro using World Bank's consumer price index (CPI). Results: There were 14 out of 368 studies included in this systematic review. Most studies were conducted from a hospital perspective, showing cost savings of T-SC ranging from €52.6 to €29,617.3 per patient annually. Quality assessments based on the CHEERS checklist revealed that the number of compliant sections or items in the studies ranged from 11 to 19 out of 24. Conclusion: This systematic review demonstrated that T-SC might offer cost savings compared to T-IV in treating HER2-positive breast cancer. However, the limited number of studies and their methodological heterogeneity highlight the need for further comprehensive research to inform decision-makers on trastuzumab use.